ON INVENTORY SYSTEM COMPUTERIZED PHARMACY CIRACAS EAST JAKARTA - Purnama Elina; Sapta Aji. SM. Skom. MM (Jurnal Sistem Informasi, 2003)
In a system that is currently running there are still many shortcomings, among others,namely the lack of controlling the supply of drugs and expired medicines, so it tooktoo long to seek information on each type of drug and preparing reports.From these deficiencies by applying the most precise computerized consideredbecause with the computer controlling the supply of medicines and expired drugs canbe more easily performed and can provide information and preparing reports faster.